2015
DOI: 10.1128/jvi.02455-14
|View full text |Cite
|
Sign up to set email alerts
|

Lethal Coinfection of Influenza Virus and Streptococcus pneumoniae Lowers Antibody Response to Influenza Virus in Lung and Reduces Numbers of Germinal Center B Cells, T Follicular Helper Cells, and Plasma Cells in Mediastinal Lymph Node

Abstract: Secondary Streptococcus pneumoniae infection after influenza is a significant clinical complication resulting in morbidity and sometimes mortality. Prior influenza virus infection has been demonstrated to impair the macrophage and neutrophil response to the subsequent pneumococcal infection. In contrast, how a secondary pneumococcal infection after influenza can affect the adaptive immune response to the initial influenza virus infection is less well understood. Therefore, this study focuses on how secondary p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 41 publications
2
23
0
2
Order By: Relevance
“…Whereas Wolf et al (2014) described increased levels of virus-specific IgG in a rather mild murine model of postinfluenza bacterial pneumonia, others found a severe impairment of IgG, IgM and IgA production in co-infected mice (Wu et al, 2015). These contrasting findings have mainly been explained with differences in the experimental models (sub-lethal vs lethal co-infection).…”
Section: Impairment Of Antibody-mediated Immunitymentioning
confidence: 75%
See 1 more Smart Citation
“…Whereas Wolf et al (2014) described increased levels of virus-specific IgG in a rather mild murine model of postinfluenza bacterial pneumonia, others found a severe impairment of IgG, IgM and IgA production in co-infected mice (Wu et al, 2015). These contrasting findings have mainly been explained with differences in the experimental models (sub-lethal vs lethal co-infection).…”
Section: Impairment Of Antibody-mediated Immunitymentioning
confidence: 75%
“…Blevins et al (2014) found that co-infection of influenza-infected mice with S. pneumoniae affects the ongoing T-cell response to the virus not only by reducing the number of virus-specific CD8 + T-cells in the lungs, but also by reducing their cytokine production. Likewise, Wu et al (2015) showed the CD4 + T-cell population to be reduced during post-influenza pneumococcal infection. Moreover, influenza virus infection has been demonstrated to impair the release of IL-17 by TH17 cells and IL-17-producing gd T-cells during secondary infection of mice with bacteria (Kudva et al, 2011;Li et al, 2012).…”
Section: Alveolar Macrophages (Ams)mentioning
confidence: 99%
“…More precisely, S. pneumoniae was found to mediate a significant reduction in the formation of Ag-specific splenic T follicular helper and germinal center B cells and antibody-secreting cells in the spleen and bone marrow in response to OVA32. Similarly, in a lethal coinfection model of influenza virus and S. pneumoniae , coinfection caused depletion of CD4 + T cells and B cells in mediastinal lymph nodes and spleen, with concomitant reduction in virus-specific antibody responses33. In this regard, a transient depletion of CD4 + T cells in the spleen was observed during a primary S. suis infection.…”
Section: Discussionmentioning
confidence: 95%
“…In reported in vivo models of co-infection, animals are commonly challenged with S. pneumoniae 3-7 days after IAV, corresponding to the most pronounced changes to morbidity and mortality (100,182). However, influenza still predisposes mice to S. pneumoniae infection at later times of challenge, and clinically there are positive correlations between influenza and severe pneumococcal pneumonia with up to 4 weeks separating the two infectious agents, suggesting the IAV imparts long term effects in the host (183,184).…”
Section: Impact Of Iav-pneumococci Co-infection On Immune Defense At mentioning
confidence: 99%